Recent Advances in the Extraction of Pittosporum angustifolium Lodd. Used in Traditional Aboriginal Medicine: A Mini Review - Beh, Chau Chun; Teoh, Wen Hui (MDPI, 2022)
Numerous native Australian plants are widely used as traditional medicines by the Australian Aboriginal and Torres Strait Islander peoples. Among the native plants, Pittosporum angustifolium Lodd. (Gumby Gumby) is claimed to be a promising medicinal plant in the treatment of a wide range of diseases that includes viral symptoms (colds and coughs), eczema, cancer, muscle aches, varicose veins, and many more. Various extraction techniques are used to extract the bioactive compounds of P. angustifolium, which are formulated into nutraceuticals. The present paper will provide an overview of the recent development in the extraction of bioactive ingredients from P. angustifolium, as well as the findings on the phytochemicals and antimicrobial activity of P. angustifolium extracts.